Epidemiologic Study of Patients Registered in Oncology Unit at a Hepatobiliary Tertiary Care Center in India - Sharma, Namita; Kumar, Guresh; Sahai, Puja; Yadav, Hanuman Prasad (Indian Journal of Medical and Paediatric Oncology, 2020)
Background: Cancer accounts for about 1 in 7 deaths, worldwide. Primary cancers of the hepatobiliary system are significant health problems worldwide and their management presents great challenges for the hepatobiliary specialist. The incidence of hepatobiliary malignancies is on an increasing trend in India. Study: We did a retrospective study for the epidemiologic, clinical characteristics, and outcomes of patients with cancer registering for treatment in the oncology division at the Institute of Liver and Biliary Sciences, Delhi, India, between January 1, 2017 and December 31, 2017. Results: Atotal of 502 new patients were registered during the study period. The majority of the patients were male (M:F 1.69:1), in the age group of 35–64 years (64.3%) and presented in advanced stages of the disease (72.7% in Stage III and IV). The most common cancers were gallbladder cancer (GBC) (29.7%) and hepatocellular carcinoma (HCC) (17.3%). GBC was the most common in females (M: F 1:1.6), 86.6% were advanced (Stage III and IV), and gallstones were present in 44.3% patients (M: F 1:2.9). Periampullary carcinoma presented in early stages (71% in Stage I and II). Survival at 6 months (n = 110 evaluable patients) was 100% for Stage I, 88% for Stage II, 73.7% for Stage III and 42.1% for Stage IV, and 62.7% overall (P < 0.001). Survival at 6 months (n = 123 evaluable patients) was 56.5% for biliary cancers, 71.4% for HCC, and 75% for nonbiliary cancers (P = 0.15). 217 (43%) patients had one visit to the hospital and 168 (34%) patients had 2–5 visits with no or little follow-up. Conclusions: Most of the disease burden was in the male gender (GBC was more common in females), in the age group 35–64 years and with advanced disease presentation (except periampullary cancer). Survival diminished significantly with increasing stage of disease. Survival was worse for patients with biliary cancers. This could be due to advanced presentation, poor follow-up, and inadequate public health awareness.
Keywords: Epidemiology; gallbladder cancer; hepatobiliary cancers; hepatocellular cancer; periampullary carcinoma